Packaging as an effective marketing tool for product / Fadzlina Mohd Fadzil - Mohd Fadzil, Fadzlina (Faculty of Art and Design, 2013)
Packaging is the science, art, and technology of enclosing or protecting products for distribution, storage, sale, and use. Packaging also refers to the process of design, evaluation, and production of packages. Packaging can be described as a coordinated system of preparing goods for transport, warehousing, logistics, sale, and end use. Packaging contains, protects, preserves, transports, informs, and sells. In many countries it is fully integrated into government, business, institutional, industrial, and personal use. This chapter discuss about packaging as an effective marketing tool for product. It will also examine the background of the problem, problem statement, research objective, research questions, scope of research, significant of the research, concept definition, operational definition and limitation of research. Besides that, this chapter will also be the medium to observe the packaging effect on the mean and how it attracts the viewer’s. Additionally, this research will also discuss other factors such as the impact of packaging and the buyer perception towards a interesting packaging Kerepek Ubi Pedas packaging through this proposal.